Alert notification via SMS / Zudiana Zainuddin - Zainuddin, Zudiana (Faculty of Information Technology and Quantitative Sciences, 2006)
The growth of technology of communication nowadays became the most significance to people around the world. People today rely on technology and communication because the communication is important in daily life. Technology of communication enable people to communicates in many ways and methods not only using telephone and letters but using the mobile phone, electronic mail, video conferencing and others. Mobile phone now becomes one of the necessities of people in daily life. Using mobile phone, a person can communicate and exchange information faster and reliable. One of the main features of mobile phone is its enable user to send and receive short message called Short Message System or SMS. SMS allow users to send and receive short message and users also can save, read and reply to the message. SMS provide faster and reliable transfer of message because SMS that has been sent will be received in a second by recipient. SMS also charged lower cost to a user which was within 20 to 5 cent. This project purposed to enhance the features of SMS because SMS is not only can be received from a mobile phone but also can be received from a personal computer. These projects enable SMS being sent from a personal computer to a mobile phone. A person or group that will be reflected from this project is some one that does not have ability to use a computer and mobile phone or do not have knowledge to use a personal computer. They also can gain benefits of SMS by using this project. This project provides means to those people related to it and to the researcher.